The influence of university brand personality on students’ identification and supportive intention in Vietnam: A mediator of university brand respect - Nguyen-Anh, Thu (Journal of Interdisciplinary Studies in Education, 2026)
University branding has become a crucial strategy for attracting valuable resources and increasing student enrollment. Developing expected brand personalities can enhance institutions’ appeal and students’ positive behaviours/attitudes. The study employed a questionnaire survey to collect evaluations from 396 Vietnamese students regarding the relationships among university brand personality (UBP), university brand respect (UBR), student-university identification, and students’ intentions to support their university after graduation. The results indicate that UBP has a positive yet modest impact on students’ identification and supportive intentions. UBR has a much greater positive effect on these variables. UBR mediates UBP’s influence on the other variables. The study offers recommendations for future research and managerial implications for developing brand personalities, values, and performance that resonate with students.